Semantic-based visual information retrieval - Zhang, Yu-Jin 1954- (IRM Press, Publisher of innovative scholarly and professional information technology titles in the cyberage, 2007)
"This book presents state-of-the-art advancements and developments in the field, and also brings a selection of techniques and algorithms about semantic-based visual information retrieval. It covers many critical issues, such as: multi-level representation and description, scene understanding, semantic modeling, image and video annotation, human-computer interaction, and more" - Provided by publisher